Pengaruh Jenis Pakan dan Level Pemberian Viterna sebagai Feed Suplement terhadap Organ Dalam Ayam Broiler: The Effect of Feed Type and Level of Viterna as Feed Supplement on The Internal Organs of Broiler Chickens - Bureni, Natalia Blandina; Malik, Agustinus Konda; Theedens, Jonas F. (Universitas Nusa Cendana, 2024)
This study aims to examine the effect of feed type and viterna levels in drinking water as well as the interaction of these two factors on the internal (percentage of gizzards, percentage of liver, percentage of small intestine and length of small intestine) of broiler chickens. This study used128 dayold broiler chickens. The method used is anexperimental method with a completely randomized design with a 2x4 factorial. The first factor consisted of 2 types of feed (J1=CP 11 and J2=BR 1) and The second factor was 4 viterna levels (P0= 0 cc or no viterna, P1=1.5 cc, P2=3.0 cc and P3=4.5 cc/liter of drinking water). So there are 8 treatment combinations and 4 replications, and each unit contains 4 chickens. The combination of treatments namely; J1PO= CP 11 commercial feed without the addition of viterna, J1P1= CP 11+ commercial feed 1.5 cc viterna/liter of water, J1P2= CP 11 commercial feed+ 3.0 cc viterna/liter of water, J1P3= CP 11+ 4 commercial feed .5 cc viterna/liter of water, J2P0 commercial feed BR 1 without the addition of viterna, J2P1= commercial feed BR I + 1.5 cc viterna/liter of water, J2P2= commercial feed BR I + 3.0 cc viterna/liter of water, J2P3 = BR I commercial feed + 4.5 cc of viterna/liter of water. The variables measured were gizzard percentage, liver percentage, small intestine percentage and small intestine length. The results of this study showed that there was no interaction (P> 0.05) between the treatment of the feed type factor (J) and the viterna level factor (P) for all variables. The conclusion of this research is that the different types of feed and the level of viterna feeding up to 4,5 cc do not have a singnificant effect on the internal organs (percentage of gizzards, percentage of liver, percentage of small intestine and length of small intestine) of broiler chickens and there are no interantions between both factors. Penelitian ini bertujuan untuk mengkaji pengaruh jenis pakan dan level viterna dalam air minum serta interaksi kedua faktor terhadap organ dalam (persentase rempela, persentase hati, persentase usus halus dan panjang usus halus) ayam broiler. Penelitian ini menggunakan sebanyak 128 ekor ayam broiler umur sehari. Metode yang digunakan adalah metode eksperimen dengan rancangan acak lengkap pola faktorial 2x4. Faktor pertama terdiri dari 2 jenis pakan (J1=CP 11 dan J2= BR 1) dan faktor kedua 4 level viterna (P0= 0 cc, P1=1,5 cc, P2=3,0 cc dan P3=4,5 cc/liter air minum). Setiap kombinasi perlakuan diulang 4 kali dan setiap ulangan terdapat 4 ekor ayam. Variabel yang diukur adalah persentase rempela, persentase hati, persentase usus halus dan panjang usus halus. Hasil penelitian ini menunjukkan tidak adanya interaksi (P>0,05) antara perlakuan faktor jenis pakan (J) dan faktor level viterna (P) terhadap semua variabel. Kesimpulan dari penelitian ini adalah faktor perbedaan jenis pakan dan faktor level pemberian viterna hingga 4,5 cc tidak memberi pengaruh yang singnifikan terhadap organ dalam (persentase rempela, persentase hati, persentase usus halus dan persentase panjang usus) ayam broiler, serta tidak ada interaksi antar kedua faktor